The Use of Comic Strip as Media to Increasing the Students' Vocabulary Mastery at SMKN 4 Pangkep - Amir, Veranda; Hamid, Sitti Maryam; Azis, Awalia (FKIP Unismuh Makassar, 2024)
This study aims to determine the increase in students' vocabulary skills by using comics as a medium to improve students' vocabulary skills in terms of reading This study focuses on the use of comic strips as a medium to improve students' vocabulary. The type of research used is Pre-Experimental Research. This aims to determine the effectiveness of using comic strip media to improve vocabulary understanding for class XI students of SMKN 4 Pangkep for the 2022/2023 academic year. The sample of this study were students majoring in offices, amounting to 27 students of class XI offices at SMKN 4 Pangkep. This study used a purposive sampling technique using the pre-experimental method. Researchers obtained data by using pre-test and post-test.The average value of the pre-test was (56.29) and the post-test was (75.74). That is a better improvement than the average student's score on the post-test. Based on the results of the analysis, it was concluded that the use of comic media can improve the vocabulary understanding of class XI students of SMKN 4 Pangkep.